Vocabulary Acquisition in EFL: A Literature Review of Innovative Vocabulary Teaching Strategies - Gede Sutrisna (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2021)
In language learning, it is important for teachers to have in-depth consideration onthe strategy of teaching vocabulary. It is advised to choose a strategy which brings lots ofbenefits for students’ vocabulary acquisition. The strategy not only should facilitate thestudents to achieve the learning objectives, but also provide them with enjoyable andmeaningful activities. It must be able to challenge the students so that they can activelyand creatively participate during vocabulary teaching learning process. When they areinvolved, they are receiving, understanding and using the material given. Thoseprocesses will effectively promote their comprehension and vocabulary development. Thepurpose of this paper is to explore three innovative strategies for teaching vocabulary:Flip-a-Chip, Word Ladders and The Ripple Effect.